2018
DOI: 10.5505/ktd.2018.27146
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Of Health Literacy Of Reading Students In Social And Health Sciences Of A University

Abstract: I In nv ve es st ti ig ga at ti io on n o of f H He ea al lt th h L Li it te er ra ac cy y o of f R Re ea ad di in ng g S St tu ud de en nt ts s i in n S So oc ci ia al l a an nd d H He ea al lt th h S Sc ci ie en nc ce es s o of f a a U Un ni iv ve er rs si it ty y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
2
12
1
Order By: Relevance
“…A number of studies carried out by Zhang et al with the students at faculties of medicine and nursing as well as a study carried out in Pakistan with faculty of pharmacy students suggested that as students' age and the year at school went up, so did their health literacy rate [10,18,20]. Similar other studies conducted with students enrolled in faculties of health sciences, nursing and medicine in our country are also supportive of our findings [21][22][23]. This may be due to the fact that as students' year in school and age went up, the health-related education they receive becomes more advanced as they move up in years.…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies carried out by Zhang et al with the students at faculties of medicine and nursing as well as a study carried out in Pakistan with faculty of pharmacy students suggested that as students' age and the year at school went up, so did their health literacy rate [10,18,20]. Similar other studies conducted with students enrolled in faculties of health sciences, nursing and medicine in our country are also supportive of our findings [21][22][23]. This may be due to the fact that as students' year in school and age went up, the health-related education they receive becomes more advanced as they move up in years.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, no significant relationship was found between the students' mean age and their AHLS scores (p>0.05). Although there are studies that did not find a relationship between age and health literacy (28,29), a positive correlation was found between age and health literacy This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to level in a study conducted with health and social science students (30). The reason for the different results pertaining to the relationship between health literacy level and age may be that all students, regardless of their age, are freshmen when their education level is considered.…”
Section: Discussionmentioning
confidence: 98%
“…Among the similar studies performed with the health literacy scale for adults, Dinçer and Kurşun [14] reported a mean adult health literacy score of 14.31±2.60 in university students. İnkaya and Tüzer [15] found this score as 16.9±3.2 in university students from Health and Social Sciences while Gül et al [16] reported a score of 13.9±2.65 in a sample consisting of university students in vocational school. In a study conducted in Iran with 250 subjects, 50.4% of the participants were found to have an insufficient level of health literacy, and a study in 386 students in the field of health revealed that 50.5% of the participants had sufficient health literacy levels [17,18].…”
Section: Discussionmentioning
confidence: 99%